The influence of experiential knowledge and societal perceptions on decision-making regarding non-invasive prenatal testing (NIPT) - Sophie Montgomery; Zaneta M. Thayer (BMC, 2020)
Abstract Background Non-invasive prenatal testing (NIPT) allows women to access genetic information about their fetuses without the physical risk inherent to prior testing methods. The advent of NIPT technology has led to concerns regarding the quality and process of informed consent, as a view of NIPT as "routine" could impair women's considered approach when choosing to undergo testing. Prior studies evaluating NIPT decision-making have focused on the clinical encounter as the primary environment for acquisition of biomedical information and decision formation. While important, this conceptualization fails to consider how additional sources of knowledge, including embodied and empathetic experiential knowledge, shape perceptions of risk and the societal use of NIPT. Methods In order to address this issue, qualitative, semi-structured interviews with 25 women who had been offered NIPT were performed. Participants came from a well-resourced, rural setting near a major academic medical center in the US. Women were categorized by NIPT use/non-use as well as whether their described decision-making process was perceived as making a significant decision requiring contemplation ("significant") versus a rapid or immediate decision ("routinized"). A constructivist general inductive approach was used to explore themes in the data, develop a framework of NIPT decision-making, and compare the perceptions of women with differential decision-making processes and outcomes. Results A framework for decision-making regarding NIPT was developed based on three emergent factors: perceptions of the societal use of NIPT, expected emotional impact of genetic information, and perceived utility of genetic information. Analysis revealed that perceptions of widespread use of NIPT, pervasive societal narratives of NIPT use as "forward-thinking," and a perception of information as anxiety-relieving contributed to routinized uptake of NIPT. In contrast, women who displayed a lack of routinization expressed fewer stereotypes regarding the audience for NIPT and relied on communication with their social networks to consider how they might use the information provided by NIPT. Conclusions The findings of this study reveal the societal narratives and perceptions that shape differential decision-making regarding NIPT in the U.S. context. Understanding and addressing these perceptions that influence NIPT decision-making, especially routinized uptake of NIPT, is important as the use and scope of this technology increases.